Respuesta :

Simplifying

3x + -7 = -1x + 15

Reorder the terms:

-7 + 3x = -1x + 15

Reorder the terms:

-7 + 3x = 15 + -1x

Solving

-7 + 3x = 15 + -1x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add 'x' to each side of the equation.

-7 + 3x + x = 15 + -1x + x

Combine like terms: 3x + x = 4x

-7 + 4x = 15 + -1x + x

Combine like terms: -1x + x = 0

-7 + 4x = 15 + 0

-7 + 4x = 15

Add '7' to each side of the equation.

-7 + 7 + 4x = 15 + 7

Combine like terms: -7 + 7 = 0

0 + 4x = 15 + 7

4x = 15 + 7

Combine like terms: 15 + 7 = 22

4x = 22

Divide each side by '4'.

x = 5.5

Simplifying

x = 5.5